Correction: Barriers to care for dependent older adults: Brazilian Primary Health Care managers' perspective. - Jonas Loiola Gonçalves; Raimunda Magalhães da Silva; Girliani Silva de Sousa; Indara Cavalcante Bezerra; Christina César Praça Brasil; Luiza Jane Eyre de Souza Vieira; Fernanda Colares de Borba Netto; José Maria Ximenes Guimarães; Maria Cecilia de Souza Minayo (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0309309.].